2020
DOI: 10.3390/app10165593
|View full text |Cite
|
Sign up to set email alerts
|

Event Detection of Muscle Activation Using an Electromyogram

Abstract: In this study, we proposed a precise onset and offset detection algorithm for muscle activation by using an electromyogram (EMG). The adaptive threshold was determined using the constant false alarm rate algorithm. The EMG signal was refined by morphological hole filling, which is used to close up and fill out missing information. By exploiting the EMG amplitude ratio in two channels, we significantly improved the offset detection performance. The proposed method does not require a training process, unlike con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…A recent and exciting study proposes an onset and offset detection algorithm for muscle activation validated during hand-close movement of 10 subjects [27]. It is worth noticing that the outcomes of the present study are at least comparable, in terms of MAE ± SD, with those reported in [27], although the algorithm is tested on a different dataset and in a different experimental condition. These results further support the reliability of the present algorithm in detecting muscle onset in time domain.…”
Section: B Real Semg Signalsmentioning
confidence: 59%
See 3 more Smart Citations
“…A recent and exciting study proposes an onset and offset detection algorithm for muscle activation validated during hand-close movement of 10 subjects [27]. It is worth noticing that the outcomes of the present study are at least comparable, in terms of MAE ± SD, with those reported in [27], although the algorithm is tested on a different dataset and in a different experimental condition. These results further support the reliability of the present algorithm in detecting muscle onset in time domain.…”
Section: B Real Semg Signalsmentioning
confidence: 59%
“…Thus, the concomitance of these results allows asserting that the capability of the two algorithms in detecting onset/offset events in simulated sEMG signals is comparable. Moreover, it is worth reminding that the analysis of the algorithm performances in time domain is achieved not to demonstrate that the proposed algorithm is able to outperform the other approaches in assessing onset and offset events in time domain, but just to show that the CWT algorithm is reliable in time domain since it can provide an assessment of onset and offset events at least comparable with reference algorithm reported in the literature [23,27,39,46,47]. The actual aim of the present study is, indeed, to propose an algorithm able to provide further and new information, that is, the frequency content of every single activation detected in time domain, as highlighted in the following section C.…”
Section: A Simulated Semg Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…This characteristic can be used to eliminate the time latencies of the exoskeleton control loop. In contrast to other sEMG analysis methods, onset detection has low demands towards computational power and robustness of measurements, due to its low complexity [4,20,21].…”
Section: Introductionmentioning
confidence: 99%